CALCULATIONS OF DOUBLE IMPURITY DIFFUSION IN INTEGRATED CIRCUIT PRODUCTION - V. A. Bondarev (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
Analytical formulae for calculating simultaneous diffusion of two impurities in silicon are presented. The formulae are based on analytical solutions of diffusion equations that have been obtained for the first time by the author while using some special mathematical functions. In contrast to usual formal mathematical approaches, new functions are determined in the process of investigation of real physical models. Algorithms involve some important relations from thermodynamics of irreversible processes and also variational thermodynamic functionals that were previously obtained by the author for transfer processes. Calculations considerably reduce the time required for development of new integrated circuits.